Development, Content Validity, and User Review of a Web-based Multidimensional Pain Diary for Adolescent and Young Adults With Sickle Cell Disease. Issue 6 (June 2015) - Bakshi, Nitya; Stinson, Jennifer N.; Ross, Diana; Lukombo, Ines; Mittal, Nonita; Joshi, Saumya V.; Belfer, Inna; Krishnamurti, Lakshmanan
Abstract : Background: Vaso-occlusive pain, the hallmark of sickle cell disease (SCD), is a major contributor to morbidity, poor health-related quality of life, and health care utilization associated with this disease. There is wide variation in the burden, frequency, and severity of pain experienced by patients with SCD. As compared with health care utilization for pain, a daily pain diary captures the breadth of the pain experience and is a superior measure of pain burden and its impact on patients. Electronic pain diaries based on real-time data capture methods overcome methodological barriers and limitations of paper pain diaries, but their psychometric properties have not been formally established in patients with SCD. Objectives: To develop and establish the content validity of a web-based multidimensional pain diary for adolescents and young adults with SCD and conduct an end-user review to refine the prototype. Materials and Methods: Following identification of items, a conceptual model was developed. Interviews with adolescents and young adults with SCD were conducted. Subsequently, end-user review with use of the electronic pain diary prototype was conducted. Results: Two iterative cycles of in-depth cognitive interviews in adolescents and young adults with SCD informed the design and guided the addition, removal, and modification of items in the multidimensional pain diary. Potential end-users provided positive feedback on the design and prototype of the electronic diary. Conclusion: A multidimensional web-based electronic pain diary for adolescents and young adults with SCD has been developed and content validity and initial end-user reviews have been completed.